Determination of the Medical Equipment Delivery Route for PT Tri Sapta Jaya Using Simulated Annealing (SA) Algorithm - Rizal, Muhammad Alde; Hardiman, Hendi Dwi; Diningrat, Mohammad Santosa Mulyo; Saidatuningtyas, Ifa (PT. Riset Press International, 2024)
This research was conducted at PT Tri Sapta Jaya, a medical equipment distributor company. The product distribution to consumers was inefficient due to using traditional methods. The division of regions and determination of delivery routes was based on districts and cities. The existing delivery method faced various challenges, including delivery delays and inefficient routes. This inefficiency results in potential financial losses for the company in terms of delivery costs. To assist the company in improving delivery efficiency, this research focuses on determining vehicle routes considering vehicle capacity (Capacity Vehicle Routing Problem). In solving and searching for solutions, the research uses Simulated-Annealing algorithm. The algorithm generated an initial solution randomly and improved the solution by changing the positions of consumers within a route and switching positions of consumers between routes to obtain the best solution. The computation time of the developed Simulated Annealing algorithm was quite efficient, taking only 2 seconds for 25 consumers. Based on the data from PT Tri Sapta Jaya, the best solution obtained was 615,319. This result was achieved using the Simulated Annealing algorithm with the parameters T0 = 100,000, Ta = 1, and α = 0.9.